2015
DOI: 10.1039/c5cc02599k
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared-responsive gold nanorod/liquid crystalline elastomer composites prepared by sequential thiol-click chemistry

Abstract: A novel NIR-responsive GNR/LCE composite fiber material was prepared by a three-step sequential thiol-click chemistry approach. Taking advantage of GNRs' significant photo-thermal effect, a GNR/LCE composite material with a very low Au loading-level (0.09 wt%), under 808 nm NIR stimulus achieved the N-to-I transition and shrank dramatically in an ambient environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 61 publications
(15 reference statements)
0
54
0
1
Order By: Relevance
“…In order to control the actuation of LCPs in a remotely controlled and precisely manipulated way, light has been employed to trigger the order–disorder transition of liquid‐crystal mesogens. To this end, using the photothermal effect is effective and convenient, which consists of doping the LCP matrix with a light‐absorbing and heat‐releasing active species, such as carbon nanotubes, graphene, polydopamine nanoparticles, organic dyes, conjugated polymers, and gold nanocrystals . On the other hand, for LCPs containing azobenzene mesogens, the reversible trans – cis photoisomerization of the photoswitch has been extensively explored for LCP actuators that can perform sophisticated biomimetic motions, such as bending, rolling, walking, swimming,[1a,22] oscillating, twisting, and making waves .…”
mentioning
confidence: 99%
“…In order to control the actuation of LCPs in a remotely controlled and precisely manipulated way, light has been employed to trigger the order–disorder transition of liquid‐crystal mesogens. To this end, using the photothermal effect is effective and convenient, which consists of doping the LCP matrix with a light‐absorbing and heat‐releasing active species, such as carbon nanotubes, graphene, polydopamine nanoparticles, organic dyes, conjugated polymers, and gold nanocrystals . On the other hand, for LCPs containing azobenzene mesogens, the reversible trans – cis photoisomerization of the photoswitch has been extensively explored for LCP actuators that can perform sophisticated biomimetic motions, such as bending, rolling, walking, swimming,[1a,22] oscillating, twisting, and making waves .…”
mentioning
confidence: 99%
“…1b,c. The top layer, also assigned as the main skeleton, possesses a uniaxially aligned LCE matrix incorporated with azobenzene chromophores and a near-infrared absorbing dye, so that the main skeleton of this material can execute bending under ultraviolet stimulus and shrinking under near-infrared stimulus40 because of the azobenzene cis – trans isomerization effect and the photothermal heating effect214142434445464748, which would induce the LC-to-isotropic phase transition, respectively, whereas the bottom monodomain LCE layer, which was obliquely glued on the main skeleton, has no azobenzene moieties but the near-infrared dye, so that it can only respond to near-infrared stimulus, and contributed a twisting power for the whole material to helically curl, because the shrinkage directions of the top and bottom layer are tilted to each other. The different overlapped angles between the top and bottom layers (45° or −45°) can force the material to perform right-handed or left-handed helical curling.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that gold nanorod is a good candidate for the development of LC elastomer based high‐performance photothermal actuators. Yang et al prepared GNR containing LC elastomer composites using thiol‐click chemistry . These elastomeric composites exhibited responsiveness to NIR and underwent nematic to isotropic phase transition under NIR irradiation.…”
Section: Liquid Crystals Driven By Photothermal Effectmentioning
confidence: 99%